2020
DOI: 10.1029/2020jb019771
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Liquid Phase on Force Distribution During Deformation in a Granular System

Abstract: Two‐phase systems, where one phase is solid and the other is fluid, are widespread in nature. Examples include reservoir rocks holding vital fluids like water or petroleum, slurries of partially crystallized magmas, fluids migrating along faults filled with fault gouge, and even the semibrittle crust. Previous studies of two‐phase systems have shown that the fluid phase plays an important role in deformation localization and dynamics (e.g., Higashi & Sumita, 2009, https://doi.org/10.1029/2008JB005999; Reber et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
(111 reference statements)
1
13
0
Order By: Relevance
“…The resemblance between our semi-brittle experiments and viscous creep is not unexpected as previous studies show that the presence of a viscous interstitial fluid can redistribute stress rather effectively (Fusseis et al, 2006;Reber et al, 2014;Webber et al, 2018;Beall et al, 2019;Ladd and Reber, 2020). The dispersion of stress can occur by the viscous fluid transferring stress to surrounding force chains or by the formation of shear planes within the fluid itself.…”
Section: Force Measurementssupporting
confidence: 81%
See 1 more Smart Citation
“…The resemblance between our semi-brittle experiments and viscous creep is not unexpected as previous studies show that the presence of a viscous interstitial fluid can redistribute stress rather effectively (Fusseis et al, 2006;Reber et al, 2014;Webber et al, 2018;Beall et al, 2019;Ladd and Reber, 2020). The dispersion of stress can occur by the viscous fluid transferring stress to surrounding force chains or by the formation of shear planes within the fluid itself.…”
Section: Force Measurementssupporting
confidence: 81%
“…Even in a system The brittle and viscous phases accommodate strain c) Supportive framework formed by the brittle phase that resembles a granular system. Adapted from Handy (1990) with a high brittle phase concentration, the rheological properties of the viscous phase, however, can still impact strain localization and deformation dynamics (Higashi and Sumita, 2009;Reber et al, 2014;Ladd and Reber, 2020).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Semi‐frictional numerical experiments with constant viscosity matrix suggest that high viscosity contrasts between the matrix and the clasts can effectively lower the bulk shear stress required for clast failure (Beall et al., 2019a). In addition, analog experiments on elastic clasts embedded in a linear viscous matrix have shown that the matrix was able to sustain differential stresses over extended periods of time (Ladd & Reber, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For clast concentrations higher than 50% by volume, clasts can interact with each other and force chains or stress bridges can form (Beall et al., 2019a; Webber et al., 2018). In cases where the clast concentration is smaller, direct coupling between the viscous matrix material and the clasts, and matrix properties that can temporarily sustain differential stresses (Ladd & Reber, 2020) would be necessary to transfer stresses leading to the potential failure of clasts (Phillips et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation